1996
DOI: 10.1007/bf00181131
|View full text |Cite
|
Sign up to set email alerts
|

MR cholangiopancreatography (MRCP) at 0.5 T: technique optimisation and preliminary results

Abstract: The aim of our study was to evaluate the feasibility of MR cholangiopancreatography (MRCP) at 0.5 T. To our knowledge no previous studies of MRCP have been performed at mid-field strength. Thirty-one patients with dilated biliary systems were examined with three-dimensional MRCP. All patients were studied with a 0.5 T superconducting magnet. A three-dimensional turbo spin-echo (TSE) sequence was acquired (TR = 5000 ms, TE = 244 ms, echo train length = 45; acquisition time = 14 min 10 s). Coronal images were po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Resolution may be further improved by using a surface coil and a smaller FOV [19] or a multicoil array and an image matrix of 512 × 256 pixels [22]. Pavone et al have shown that MRCP images of good quality can also be obtained with the body coil of a 0.5-T system by using a matrix size of 83 × 128 [23]. Acquisition of volumetric (3D) FSE data sets has recently become possible with some equipment [20,23].…”
Section: Technical Considerationsmentioning
confidence: 98%
See 3 more Smart Citations
“…Resolution may be further improved by using a surface coil and a smaller FOV [19] or a multicoil array and an image matrix of 512 × 256 pixels [22]. Pavone et al have shown that MRCP images of good quality can also be obtained with the body coil of a 0.5-T system by using a matrix size of 83 × 128 [23]. Acquisition of volumetric (3D) FSE data sets has recently become possible with some equipment [20,23].…”
Section: Technical Considerationsmentioning
confidence: 98%
“…Pavone et al have shown that MRCP images of good quality can also be obtained with the body coil of a 0.5-T system by using a matrix size of 83 × 128 [23]. Acquisition of volumetric (3D) FSE data sets has recently become possible with some equipment [20,23]. In comparison with the multislice (2D) FSE technique, the 3D technique allows not only to obtain high-quality MIP reconstructions in all planes from a single acquisition, but also to reduce the slice thickness to 2 mm or less, if necessary.…”
Section: Technical Considerationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The high sensitivity ofMRCP for abnormalities of the biliary tree and pancreatic duct system has been reported (11)(12)(13)(14)(15)(16). MRCP provides both high-quality cross-sectional images of extraductal structures and projectional images of the biliary tree and pancreatic duct system without any oral or intravenous contrast materials.…”
Section: Discussionmentioning
confidence: 99%